2018
DOI: 10.21037/jtd.2018.04.52
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy (SBRT) for early stage non-small cell lung cancer (NSCLC): contemporary insights and advances

Abstract: The standard-of-care treatment for early-stage non-small cell lung cancer (NSCLC) continues to be surgery in the form of lobectomy or pneumonectomy. Stereotactic body radiation therapy (SBRT) has evolved as a viable alternative to surgery for medically inoperable patients, achieving excellent local control (LC) with relatively minimal toxicity in standard-risk patients. Nevertheless, the maturation of SBRT has fostered debate regarding its use, technique, dose, and fractionation, particularly in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 113 publications
(141 reference statements)
1
33
0
2
Order By: Relevance
“…One died of esophageal perforation causing mediastinitis, and the other patient had a tracheoesophageal fistula. The last study reported 8% (14 of 182 patients) high-grade esophageal toxicity after treatment with single-fraction SBRT (16)(17)(18)(19)(20)(21)(22)(23)(24) to metastases abutting the esophagus. In this study a D 2.5cc <14 Gy (47.6 Gy EQD 2Gy,3Gy ) was suggested to Abbreviations: COPD GOLD Z classification of Chronic Obstructive Pulmonary Disease; IQR Z interquartile range; WHO Z World Health Organization; 95% CI Z 95% confidence interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One died of esophageal perforation causing mediastinitis, and the other patient had a tracheoesophageal fistula. The last study reported 8% (14 of 182 patients) high-grade esophageal toxicity after treatment with single-fraction SBRT (16)(17)(18)(19)(20)(21)(22)(23)(24) to metastases abutting the esophagus. In this study a D 2.5cc <14 Gy (47.6 Gy EQD 2Gy,3Gy ) was suggested to Abbreviations: COPD GOLD Z classification of Chronic Obstructive Pulmonary Disease; IQR Z interquartile range; WHO Z World Health Organization; 95% CI Z 95% confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…First, higher rates of toxicity are suggested in patients treated on consecutive days compared with patients treated on nonconsecutive days. 21 Additionally, esophageal motion could result in a different delivered dose compared with the planned dose. This can lead to higher esophageal doses, which in turn may result in unexpected occurrence of toxicity.…”
Section: Probability Of Late Grade 3-5 Esophageal Toxicity (%) Equivamentioning
confidence: 99%
“…Apesar do tratamento padrão do CPNPC em estadio inicial continuar a ser a cirurgia, a SBRT evoluiu no sentido de se tornar uma alternativa viável nos doentes medicamente inoperáveis ou de elevado risco operatório, demonstrando excelentes controlos locais, com toxicidade mínima, nos doentes de risco padrão 22 .…”
Section: Radioterapia Estereotáxica Fraccionada (Sbrt)unclassified
“…De uma coorte de 42 doentes estudados, a maioria apresentava tumores em estadio I -II (81%) e recebeu tratamento com SBRT (74%). A incidência de recidiva local aos 30 meses foi de 70% se mutação KEAP1/NRF2 vs 18% nos tumores não mutados 85,86 .…”
Section: Preditores Moleculares Biomarcadores De Resposta E Radiogenunclassified
“…Though considered a relatively safe surgery with low overall morbidity and mortality [2], inherent surgical risks still remain. For those who are deemed poor surgical candidates, stereotactic body radiotherapy (SBRT) is a less invasive alternative that has been associated with excellent local control [3]. SRBT, however, is costly and includes side effects such as pneumonitis.…”
mentioning
confidence: 99%